Climate History of Hungary Since 16th Century: Past, Present and Future - Rácz, Lajos (Discussion Papers, 1999)
The author of the present paper after tracing the territorial variations of Hungary since 1990 AD, analyzes the climate history of Hungary based on various documentary sources taken from Réthly’s Source Book (chronicles, articles, public administration records, private estate records, early journalism, early instrument based records, personal papers and meteorological instrument records). To combine the historical climate information from the various documentary sources with that in the author’s routine climate analysis, the sources had to be rearranged according to theme, geographical location and dates. To facilitate this procedure the author used the program of the Clim-Hist computer climate history databank. The final chapter of the study contains the most significant elements of the author’s research regarding climate history in which he attempts to explore the inner structure of the climate changes in the Carpathian Basin with the help of correlation studies. It also contains a summary of the specific features of the climate change in the Little Ice Age and during the recent warming. Finally a prognosis is established of the expected direction and characteristics of future changes in climate.